2008
DOI: 10.1002/app.28283
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polymer‐brush‐type polysaccharide β‐ketoesters

Abstract: Polyvinyl alcohol (PVA) and four glucans, cellulose, curdlan, amylase, and pullulan, were dissolved in 8% lithium chloride/1,3-dimethyl-2-imidazolodinone, and reacted with ketene dimers with long alkyl or alkenyl chains under homogeneous conditions. The corresponding polysaccharide b-ketoesters with degrees of substitution (DS) of 2.1-2.9 and the PVA b-ketoester with DS 0.9 were prepared in the yields of 80-90%. Solution-state 1 H-and 13 C-NMR spectra of the polysaccharide and PVA b-ketoesters revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Thus, the 1 H-and 13 C-NMR spectra of the cellulose b-ketoesters look like simple alkanes or alkenes, and no information concerning DS, DS distribution among the C2, C3 and C6 hydroxyls of cellulose or others could be obtained from their NMR spectra. Such anomalous NMR patterns were observed also for polysaccharide b-ketoesters with DS 2.3-2.9 prepared from pullulan, amylose and curdlan (Yoshida and Isogai 2008). Moreover, a polyvinyl alcohol b-ketoester with DS 0.9 also showed similar NMR patterns.…”
Section: Introductionsupporting
confidence: 52%
“…Thus, the 1 H-and 13 C-NMR spectra of the cellulose b-ketoesters look like simple alkanes or alkenes, and no information concerning DS, DS distribution among the C2, C3 and C6 hydroxyls of cellulose or others could be obtained from their NMR spectra. Such anomalous NMR patterns were observed also for polysaccharide b-ketoesters with DS 2.3-2.9 prepared from pullulan, amylose and curdlan (Yoshida and Isogai 2008). Moreover, a polyvinyl alcohol b-ketoester with DS 0.9 also showed similar NMR patterns.…”
Section: Introductionsupporting
confidence: 52%
“…These solutionstate 13 C-NMR spectra of AKOs are very similar to those of polymer-brush-type cellulose b-ketoesters with degrees of substitution of >2 prepared from cellulose via homogeneous reaction with AKDs. [4][5][6][7] In the case of the polymer-brush-type cellulose bketoesters, cellulose molecules and b-ketoester parts (except long alkyl chains) behave like solid even in solution state owing to strong restriction in their mobility via the densely introduced long alkyl chains into cellulose molecules. [4][5][6][7] The results of solution-state 13 C-NMR spectra of AKOs also indicated that the connection parts of the repeating units were strongly restricted in mobility.…”
Section: As Shown Inmentioning
confidence: 99%
“…[4][5][6][7] In the case of the polymer-brush-type cellulose bketoesters, cellulose molecules and b-ketoester parts (except long alkyl chains) behave like solid even in solution state owing to strong restriction in their mobility via the densely introduced long alkyl chains into cellulose molecules. [4][5][6][7] The results of solution-state 13 C-NMR spectra of AKOs also indicated that the connection parts of the repeating units were strongly restricted in mobility. If AKOs have linear chemical structures consisting of the repeating units, some carbon signals due to both ends of oligomer chains should be detected in the 13 C-NMR spectra.…”
Section: As Shown Inmentioning
confidence: 99%
See 2 more Smart Citations